A comparative study of cone beam computed tomography and conventional radiography in diagnosing the extent of root resorptions - Elham Alamadi; Hisham Alhazmi; Ken Hansen; Ted Lundgren; Julia Naoumova (SpringerOpen, 2017)
Abstract Background Root resorptions are assessed and diagnosed using different radiographical techniques. A comparison of the ability to assess resorptions on two-dimensional (2D) and three-dimensional (3D) radiographs is, hitherto, lacking. The aims of this study were to evaluate the accuracy of 2D (periapical radiographs, PA and panoramic radiograph, PAN) and 3D (cone beam computed tomography, CBCT) radiographic techniques in measuring slanted root resorptions compared to the true resorptions, a histological gold standard, in addition to a comparison of all the radiographic techniques to each other. Methods Radiographs (CBCT, PA, and PAN), in addition to histological sections, of extracted deciduous canines from thirty-four patients were analyzed. Linear measurements of the most and least resorbed side of the root, i.e., "slanted" resorptions, were measured using an analyzing software (Facad ®). For classification of slanted root resorptions, a modified Malmgren index was used. Results PAN underestimated the root length on both the least and most resorbed side. Small resorptions, i.e., low modified Malmgren scores, were more difficult to record and were only assessed accurately using CBCT. The root resorption scores were underestimated using PA and PAN. In assessment of linear measures, PAN differed significantly from both CBCT and PA. Conclusions CBCT is the most accurate technique when measuring and scoring slanted root resorptions.